Application of warm acupuncture combined with scraping therapy in relief of symptoms of diabetic peripheral neuropathy and related nursing measures (温灸刮痧缓解1例糖尿病周围神经病变患者下肢症状的护理体会) - SHANG Zhihua (尚志花); LI Xin (李欣); WANG Chunhong (王春红); ZHAO Xin (赵欣); LIU Huan (刘欢); XU Weihong (徐卫红); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the treatment effect of warm acupuncture combined with scraping therapy in relief of symptoms of diabetic peripheral neuropathy and related nursing measures. A special scraping device was used to wipe smoothly along the meridians such as Liver Channel of Foot Jueyin, Kidney Channel of Foot Shaoyin, Spleen Channel of Foot Taiyang and Stomach Channel of Foot Yangming. The warm acupuncture was carried out on Zusanli, Diji, Sanyinjiao and Yongquan acupoints after scraping therapy. The cold and numbness symptoms of lower extremity and foot were relieved after implementation of warm acupuncture combined with scraping therapy. (本文总结1例运用温灸刮痧缓解糖尿病周围神经病变患者下肢和足部发凉、发麻症状的护理经验。运用温灸刮痧器的杯沿刮拭足厥阴肝经、足少阴肾经、足太阴脾经、足阳明胃经下肢巡行部位, 之后用温灸器在足三里、地机穴、三阴交及涌泉穴施灸。治疗后, 患者下肢和足部发凉、发麻症状缓解。)